(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
The present study evaluates the antioxidant activity of the different flavonoids of the fruits of Xylopia parviflora used in Cameroon as spice in common traditional dishes. The fruits were successively extracted with hexane and methanol. The isolation of flavonoids was guided by the DPPH-TLC technique. The methanol crude extract and isolated compounds were screened for antioxidant and free radical scavenging activities using DPPH radical-scavenging, β-carotene/linoleic acid and ferric reducing antioxidant power (FRAP) assays. The total phenolic content of the methanol crude extract was determined by Folin–Ciocalteu method. The DPPH-TLC technique led to the isolation of (+)-catechin (1), kaempferol 3-O-arabinofuranoside (2) and quercetin 3-O-arabinofuranoside (3) identified by NMR and mass spectra analysis. In the colorimetric DPPH test, compound 1 had the same activity (EC50 8.1µg/ml) as butylated hydroxytoluene (BHT) used as standard while compound 3 and the methanol crude extract were less active (EC50 17.2µg/ml). Compound 2 was completely inactive. The total phenolic content of the fruit extracts was 113.03 mg gallic acid equivalents per g of extract. In the carotene bleaching test at the highest concentration of 100µg/mL, the order of inhibition of β-carotene discoloration was BHT > crude extract > quercetin 3-O-arabinofuranoside (3) > catechin (1) > kaempferol 3-O- arabinofuranoside (2). In the reducing power assay, compound 3 was more active at concentrations 40-100µg/mL. The HPLC analysis of the methanol crude extract revealed the presence of compounds 1-3 and unidentified phenolic compounds. The antioxidant activity of the methanol extract is probably due to the presence of compounds 1 and 3.